2015
DOI: 10.1007/s00367-015-0401-y
|View full text |Cite
|
Sign up to set email alerts
|

Validation of impact penetrometer data by cone penetration testing and shallow seismic data within the regional geology of the Southern North Sea

Abstract: This study presents the assessment of total cone resistance from in situ deceleration measurements using the Lance Insertion Retardation meter (LIRmeter) in the Southern North Sea. The penetrometer is equipped with a measurement lance that is up to 6 m in length. The aim was to validate LIRmeter data interpretation within the regional geological context by comparison with static velocity cone penetration testing (CPT) and sub-bottom profiles. In total, 13 datasets were taken, in addition to preexisting hydroac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…and an empirical factor K ranging from 1-1.5 based on the results by Stoll et al (2007), Stark et al (2012b, and Stephan et al (2015) for high velocity impact penetrometers. K is expected to depend on the soil type and behavior during penetration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and an empirical factor K ranging from 1-1.5 based on the results by Stoll et al (2007), Stark et al (2012b, and Stephan et al (2015) for high velocity impact penetrometers. K is expected to depend on the soil type and behavior during penetration.…”
Section: Methodsmentioning
confidence: 99%
“…A goal for these tests is to relate K to a property measured directly by the penetrometer (e.g., a combination of deceleration over penetration depth and/or pore pressure). For the current data set, an uncertainty in quasi-static bearing capacity of about 15% results from the uncertainty related to K, allowing the ranging of K based on studies by Stoll et al (2007), and Stephan et al (2015) for high velocity impact D r a f t penetrometers. It should also be noted that a different choice of K would have little impact on the final conclusion drawn in this study, which are also supported by the measured deceleration records (Stoll et al 2007;Stark and Wever 2009).…”
Section: Geotechnical Characteristics and Stratificationmentioning
confidence: 99%
“…Dayal and Allen () proposed to correct the dynamic sediment strength (dynamic refers to changing penetration velocity and strain rate) for the strain rate effect, leading to a quasi‐static strength equivalent to measurements conducted at a chosen constant penetration velocity (industry standard for Cone Penetration Testing: 2 cm/s). The strain rate factor chosen for this study, f sr , is based on an empirical relation between the dynamic penetrometer penetration velocity v , which was determined from the first integration of the deceleration‐time profile, and a constant penetration rate v ref (Dayal and Allen ): fsr = 1 + K logtrue(v/vreftrue) where K is an empirical constant that can be assumed to range from 1.0 to 1.5 (Stoll et al ; Stark et al ; Stephan et al ). K = 1.25 ± 0.25 was used in this study to account for the range of suggested values.…”
Section: Methodsmentioning
confidence: 99%
“…where K is an empirical constant that can be assumed to range from 1.0 to 1.5 (Stoll et al 2007;Stark et al 2012;Stephan et al 2015). K 5 1.25 6 0.25 was used in this study to account for the range of suggested values.…”
Section: Analysis Of Deceleration Measurementsmentioning
confidence: 99%
“…There are two types of impact penetrometers available, i.e., lightweight devices for near-surface investigations [147] and huge penetrometers [148] for anchor performance evaluation. From field testing and laboratory observations, Lunne et al [146] and Stephan [149] show that quantitative measures, such as cone resistance, bearing capacity, shear strength, or void ratio, can be extracted through further processing of qualitative penetrometer data. "Chow and Airey [150] present an empirical model based on model penetrometer tests and reference triaxial tests to determine undrained shear strength of clayey soil targets and the influence of penetrator mass, penetrator tip shape, impact velocity, and the strain rate on undrained shear strength".…”
Section: Impact Penetration Based Soil Investigationmentioning
confidence: 99%